2017
DOI: 10.1186/s12860-017-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of pluripotent gene expression in murine embryonic stem cells exposed to mechanical loading or Cyclo RGD peptide

Abstract: BackgroundSelf-renewal and differentiation of embryonic stem cells (ESCs) is directed by biological and/or physical cues that regulate multiple signaling cascades. We have previously shown that mESCs seeded in a type I collagen matrix demonstrate a loss of pluripotent marker expression and differentiate towards an osteogenic lineage. In this study, we examined if this effect was mediated in part through Arginylglycylaspartic acid (RGD) dependent integrin activity and/or mechano-transduction.ResultsThe results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Cell viability was assessed by live/dead flow cytometry based on calcein/ethidium homodimer staining (see the Supporting Information for details). The on‐chip de‐emulsification did not affect cell viability (Figure D; Figure S3, Supporting Information), based on cell growth and reporter gene expression as readouts . In comparison, the de‐emulsification using the fluorosurfactant PFO (as described above and in the Supportin Information) resulted in dramatically lower cell viability that decreased by an order of magnitude with increasing amount of PFO to survival rate of ≈10% with 100% PFO.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cell viability was assessed by live/dead flow cytometry based on calcein/ethidium homodimer staining (see the Supporting Information for details). The on‐chip de‐emulsification did not affect cell viability (Figure D; Figure S3, Supporting Information), based on cell growth and reporter gene expression as readouts . In comparison, the de‐emulsification using the fluorosurfactant PFO (as described above and in the Supportin Information) resulted in dramatically lower cell viability that decreased by an order of magnitude with increasing amount of PFO to survival rate of ≈10% with 100% PFO.…”
Section: Resultsmentioning
confidence: 94%
“…The on-chip de-emulsification did not affect cell viability ( Figure 2D; Figure S3, Supporting Information), based on cell growth and reporter gene expression as readouts. [46,47] In comparison, the de-emulsification using the fluorosurfactant PFO (as described above and in the Supportin Information) resulted in dramatically lower cell viability that decreased by an order of magnitude with increasing amount of PFO to survival rate of ≈10% with 100% PFO. Consequently, the onchip de-emulsification using the developed extraction chip obviates the need for a chemical de-emulsifier, avoiding its detrimental effects on cell survival while facilitating integration of a de-emulsification step into automated workflows.…”
Section: Single Cell Encapsulation Into Hydrogel Beadsmentioning
confidence: 99%
“…Specifically, this molecule or mechanical stimulus significantly influenced ESC pluripotency by downregulating core transcription factors. Moreover, RGD peptide, by inhibiting integrin binding and, in turn, integrin expression [6], upregulated early lineage markers (mesoderm and ectoderm) by leukaemia inhibitory factor (LIF) signalling [138]. Interestingly, human ESC, expressing integrin α 6 β 1, preferentially bind human recombinant laminin-111, laminin-332, and laminin-511, which are good substrates able to maintain undifferentiated pluripotent human ESC cultures [139].…”
Section: Integrins and Ipscmentioning
confidence: 99%
“…In addition, mechanical force can lead to chromatin remodeling and altered binding of transcription factors 17 , 18 . Recent studies have also shown that application of mechanical strain can reduce the expression of pluripotency in mouse embryonic stem cells 19 , 20 . In human pluripotent stem cells (hPSCs), mechanical strain helped to maintain pluripotency through increased expression Nodal, transforming growth factor-β (TGF-β), and Activin 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%